Pax9 and Gbx2 Interact in the Pharyngeal Endoderm to Control Cardiovascular Development - Catherine A. Stothard; Silvia Mazzotta; Arjun Vyas; Jurgen E. Schneider; Timothy J. Mohun; Deborah J. Henderson; Helen M. Phillips; Simon D. Bamforth (Journal of Cardiovascular Development and Disease, 2020)
The correct formation of the aortic arch arteries depends on a coordinated and regulated gene expression profile within the tissues of the pharyngeal arches. Perturbation of the gene regulatory networks in these tissues results in congenital heart defects affecting the arch arteries and the outflow tract of the heart. Aberrant development of these structures leads to interruption of the aortic arch and double outlet right ventricle, abnormalities that are a leading cause of morbidity in 22q11 Deletion Syndrome (DS) patients. We have recently shown that Pax9 functionally interacts with the 22q11DS gene Tbx1 in the pharyngeal endoderm for 4th pharyngeal arch artery morphogenesis, with double heterozygous mice dying at birth with interrupted aortic arch. Mice lacking Pax9 die perinatally with complex cardiovascular defects and in this study we sought to validate further potential genetic interacting partners of Pax9, focussing on Gbx2 which is down-regulated in the pharyngeal endoderm of Pax9-null embryos. Here, we describe the Gbx2-null cardiovascular phenotype and demonstrate a genetic interaction between Gbx2 and Pax9 in the pharyngeal endoderm during cardiovascular development.